2012
DOI: 10.3329/jsr.v4i2.9640
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Human Skin Pathogens from Cosmetic Tools used in Beauty Saloons in Different Areas of Lahore, Pakistan

Abstract: With the surprising development across the cosmetic and personal care companies the reutilization of cosmetic tools is of a common practice. Isolation and detection of human skin pathogens from 100 samples of beauty salon tools i.e., blusher brush, face sponge and wax has been done. All the samples were examined microbiologically for the contamination of Staphylococcus aureus, Pseudomonas aeruginosa, yeast and fungus. It was observed that the percentage of Staphylococcus aureus was higher (100% in sponge, 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…This study finding was contrary to the findings of Stanley et al [ 8 ], who reported a higher bacterial contamination of dryer although clippers were part of the study. Naz et al [ 10 ] also reported 100%, 100%, and 88% of S. aureus contamination in sponge, brush, and wax, respectively, from cosmetic tools used in beauty salons from different areas of Lahore, Pakistan. The higher bacterial contaminations observed from clipper in this study could be due to the improper sterilization or the ineffectiveness of the disinfectant used by these salon operators although the majority of studied salons operators claimed to sterilize or disinfect the tools after use on each client.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study finding was contrary to the findings of Stanley et al [ 8 ], who reported a higher bacterial contamination of dryer although clippers were part of the study. Naz et al [ 10 ] also reported 100%, 100%, and 88% of S. aureus contamination in sponge, brush, and wax, respectively, from cosmetic tools used in beauty salons from different areas of Lahore, Pakistan. The higher bacterial contaminations observed from clipper in this study could be due to the improper sterilization or the ineffectiveness of the disinfectant used by these salon operators although the majority of studied salons operators claimed to sterilize or disinfect the tools after use on each client.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from California [ 12 ], two urban and two semiurban areas in South Africa [ 14 ], Cincinnati [ 15 ], and North Carolina counties, USA [ 16 ], on some tools also isolated other bacteria such as Mycobacterium fortuitum , M. chelonae , and M. mageritense . Similarly, studies from Abia state, Nigeria [ 8 ], Adamawa state, Nigeria [ 17 ], and Pakistan [ 10 ] based on in-use tools in hairdressing and barbering showed contamination by bacteria like S. aureus , Pseudomonas aeruginosa , S. epidermidis , Streptococcus spp., Enterococcus spp., and Enterobacter spp. However, fewer studies have investigated the role of salons in the spread of drug-resistant pathogens, especially in Africa.…”
Section: Introductionmentioning
confidence: 95%
“…The results of this study agree with finding of a previous study which indicated the prevalence of bacterial colonies when hand air-dryers were used in washrooms ( Alharbi et al, 2016 ). Numerous previous studies have also confirmed the presence of bacterial contamination on tools used in barber shops ( Stanley et al, 2019 , Enemuor et al, 2013 , Janmohammadi et al, 2016 , Stanley et al, 2014 , Enemuor et al, 2012 , Naz et al, 2012 , Dadashi and Dehghanzadeh, 2016 ). Table 1 shows the prevalence of MRSA in barber shops where hair dryers were used.…”
Section: Discussionmentioning
confidence: 61%
“…Pseudomonas aeruginosa contaminated 75% of the samples, while less than 50% of the samples were contaminated by yeast and other fungi. 35 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Pseudomonas aeruginosa contaminated 75% of the samples, while less than 50% of the samples were contaminated by yeast and other fungi. 35 Most of the research on assessing the role of salon tools in the spread of diseases found that these tools either were never stylized or were not cleaned between customers. Even when hygienic practices were employed, acceptable levels of sterilization were rarely applied.…”
Section: Microorganisms Isolated From Salon Toolsmentioning
confidence: 99%